Disagreement between skin prick test and specific IgE in young children. Issue 1 (30th November 2014) - Schoos, A.‐M. M.; Chawes, B. L. K.; Følsgaard, N. V.; Samandari, N.; Bønnelykke, K.; Bisgaard, H.
Abstract Background Skin prick test (SPT) and measurement of serum‐specific IgE (sIgE) level are important tools for the clinician to diagnose allergic sensitization. However, little is known about the agreement between the two methods in young children. Methods SPT and sIgE levels were assessed simultaneously for 16 common inhalant and food allergens at age ½, 1½, 4, and 6 years in 389 children from the Copenhagen Prospective Study on Asthma in Childhood2000 (COPSAC2000) at‐risk birth cohort. Agreement between the two methods for diagnosing inhalant and food allergic sensitization at the four age points was analyzed using kappa statistics. Results The prevalence of inhalant allergen sensitization increased during childhood diagnosed by both sIgE levels (0.6% to 4.2% to 18.1% to 24.8%, P < 0.0001) and SPT results (1.5% to 3.8% to 8.4% to 15.4%, P < 0.0001). In contrast, the prevalence of food sensitization increased during childhood when diagnosed from sIgE (7.8% to 12.1% to 15.0% to 18.9%, P < 0.0001), but decreased when diagnosed from SPT (5.3% to 5.1% to 3.7% to 3.0%, P = 0.05). Overall, the agreement between SPT and sIgE levels was poor to moderate (all κ‐coefficients≤0.60) and decreased from moderate to slight for food allergens by increasing age (κ‐coefficients: 0.46 to 0.31 to 0.16 to 0.14). Conclusion There is a substantial disagreement between SPT and sIgE for diagnosing allergic sensitization in young children, which increases with age for food sensitization. Choice of assessment method therefore has major impact on results with wide implications for both clinical practice and research.